Stripes Faded, Barking Silenced: Remembering Quagga - De Vos, Rick (Research Online - University of Wollongong, 2014)
The death of the last quagga on August 12, 1889 represented the loss of a long-term resident of the Artis Magistra Zoo in Amsterdam, at the time a private institution accessible only to members. The mare’s death was not recognised at the time as signifying the extinction of the quagga, largely due to the vague and general usage of the term ‘quagga’. The delay in understanding the significance of this death, and the way in which quaggas rapidly disappeared in the wild in southern Africa in the nineteenth century, have been overshadowed in scientific and historical accounts by debates concerning the classification of the quagga and its re-creation by elective breeding from plains zebra stock. This paper examines quaggas in terms of their relationships with each other and with other animals on the southern African plains, considering how they have been remembered in different contexts and reflecting on what has been lost in the light of attempts to erase and redeem their extinction.